2018
DOI: 10.30918/irjmms.62.18.012
|View full text |Cite
|
Sign up to set email alerts
|

Standard precautions: Nurses’ knowledge and use in a tertiary health institution in Southeast Nigeria

Abstract: The risk for hospital-acquired infections (HAIs) is high among nurses. This study is aimed at assessing nurses' knowledge and use of standard precautions (SP) in a tertiary health institution in Enugu, southeast Nigeria. The study was descriptive cross-sectional among nurses at University of Nigeria Teaching Hospital, Ituku-Ozalla, Enugu State. A pre-tested questionnaire was used and analysis was done using SPSS version 17. There were 290 respondents, most of them were females (91.7%), married (65.9%) and betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Literature have documented the knowledge, attitude and perception regarding standard precautions to be low among health workers in developing countries especially Nigeria (Ogoina, Pondei, Adetunji, Chima, Isichei & Gidado, 2015;Alice, Akhere, Ikponwonsa & Grace, 2013). Although a study conducted in Southeast Nigeria reported that knowledge, attitude and perception regarding standard precautions were good, the practice is suboptimal (Arinze-Onyia, Ndibuagu & Ozor, 2018).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Literature have documented the knowledge, attitude and perception regarding standard precautions to be low among health workers in developing countries especially Nigeria (Ogoina, Pondei, Adetunji, Chima, Isichei & Gidado, 2015;Alice, Akhere, Ikponwonsa & Grace, 2013). Although a study conducted in Southeast Nigeria reported that knowledge, attitude and perception regarding standard precautions were good, the practice is suboptimal (Arinze-Onyia, Ndibuagu & Ozor, 2018).…”
Section: Statement Of the Problemmentioning
confidence: 99%